Pressões ventilatórias máximas e função pulmonar em sujeitos portadores de bronquiectasias. - Santos de Faria Júnior, Newton; dos Reis dos Santos, Israel; Teixeira Fonsêca, Nina; Julioti Urbano, Jéssica; Souza Dias, Ismael; da Guia Almeida, Rafael; Marcelo Bigatão, Amilcar; Santos, Sérgio Ricardo; Studart Leitão Filho, Fernando Sérgio; Jardim, José Roberto; de Oliveira, Luis Vicente Franco (Revista Terapia Manual)
Introduction: The measurement of pulmonary function and the pressures generated by the ventilatory muscles have been of great clinical importance, besides having great potential for the diagnosis and prognosis of lung diseases. Due to airflow obstruction, irreversible dilatation of the bronchi and bronchioles, and the presence of secretion individuals with bronchiectasis may show changes in their respiratory muscles and lung capacity, leading to a diminished quality of life of these patients. Objective: To assess the pulmonary capacities and volumes and the maximum pressure of ventilatory muscles in subjects with bronchiectasis. Method: This is an observational and cross-sectional study that assessed 21 subjects with a previous diagnosis of bronchiectasis, at the Sleep Laboratory of the Rehabilitation Sciences Master’s and PhD Degree Programs, at Nove de Julho University (UNINOVE) in the city of São Paulo- Brazil. The evaluation consisted of medical history, vital signs, anthropometry, spirometry and manovacuometry. Results: The mean age was 51.57±15.11 years, 57.1% were female with a body mass index of 23.93 ± 3.75 kg/m2. There was a predominance of obstructive lung disease (52.4%) and reductions in the mean spirometric values of predicted (FVC, FEV1 and FEV1/FVC were 2.45 ± 0.87, 1.63 ± 0.76 and 66.49 ± 15.26 respectively). The mean values of maximal inspiratory pressures for females were 70.16 ± 26.60 and 95.55 ± 22.92 for males. The maximum expiratory pressures were 63.66 ± 24.34 and 105.11 ± 23.85 respectively for females and males. There was reduction in mean maximal ventilatory pressures as tuberculosis sequelae or not. Conclusion: Subjects with bronchiectasis presented a predominance of obstructive lung disease, reductions in spirometric values and maximal ventilatory pressures, either with regard to gender or etiology of bronchiectasis compared with the provisions of the Brazilian population.